Mimicking Nature: A Novel Peptide‐based Bio‐inspired Approach for Solar Energy Conversion. Issue 1 (22nd November 2013) - Gatto, Emanuela; Quatela, Alessia; Caruso, Mario; Tagliaferro, Roberto; De Zotti, Marta; Formaggio, Fernando; Toniolo, Claudio; Di Carlo, Aldo; Venanzi, Mariano
<x xml:space="preserve">Abstract</x> A bioinspired approach is applied to photoelectric conversion devices. A 310‐helical hexapeptide bearing a pyrene unit is immobilized on a gold‐covered TiO2 surface. The device is integrated for the first time in a dye‐sensitized solar cell, exhibiting stability after several measurements. The approach could have promising applications in the field of optoelectronics.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>